The Role of ICT in Learning Process of International Student at Chinese University - Mohamed, Oubibi; Wei, Zhao (International Journal of Engineering and Technology, 2018)
Information and communication technologies (ICT) have become common place entities in all aspects of life. Across the past twenty years, the use of ICT has fundamentally changed the practices and procedures of nearly all forms of endeavor within business and governance. Education is a very socially oriented activity and quality education has traditionally been associated with strong teachers having high degrees of personal contact with learners. The use of ICT in education lends itself to more student-centered learning settings. But with the world moving rapidly into digital media and information, the role of ICT in education is becoming more and more important and this importance will continue to grow and develop in the 21st century. In this paper, a literature review regarding the use of ICTs in education was provided. Effective use of ICT for Education, and international students from 90 countries participated in order to know the importance of ICT in their studies and to investigate the importance of ICT in their daily life.Â Â